Described from images: The remarkable soldier of Procryptotermes dioscurae Harris (Isoptera: Kalotermitidae) from Socotra Island - Scheffrahn, Rudolf H.; Křeček, Jan (Zootaxa, 2017)
Procryptotermes Holmgren is a modestly diverse kalotermitid genus endemic to numerous islands and archipelagos of the world’s tropical oceans (Scheffrahn & Křeček 2001). Mainland records from southern India (Bose 1979, Roonwal & Chhotani 1963, Thakur 1975), Queensland Australia (Watson and Abbey 1993), and the Yucatan Peninsula (Scheffrahn and Křeček 2001), also approximate oceanic coastlines. The soldier of Procryptotermes is distinguished from most other kalotermitids by long, sickle-shaped mandibles and a rather weak or absent frontal flange or protuberance (Krishna 1961). The winged imago of Procryptotermes is similar to that of Cryptotermes Banks in which the median vein is unsclerotized and intersects the radial sector near mid-wing. Of the fourteen described species of Procryptotermes (Scheffrahn & Křeček 2001), only one species, P. dioscurae Harris 1954, lacks a description of the soldier caste. It was described from three winged imagos collected from lights on Socotra Island, Yemen. Unlike soldiers, the imago caste is not present in the colony year round and often lacks species-level diagnostic characters. Therefore, the description of the soldier caste is highly desirable for most termite species.